Strategi kemas ulang informasi untuk peningkatan pelayanan perpustakaan di era new normal - Wahid Nashihuddin (Universitas Padjadjaran, 2021)
Information repackaging is one of the library's efforts to meet users' information needs in the new normal era. Libraries need to prepare various strategies in providing repackaging products as a library service innovation. This research aimed to describe various aspects and stages of library strategy design in information repackaging in the New normal era. The research used a qualitative approach through literature studies research methods. The results showed that libraries and librarians in the new normal era needed to pay attention to various aspects and stages in designing a digital information repackaging strategy. Aspects of the information repackaging strategy include determining the source of packaging information, types of information repackaging products, and information repackaging methods. Libraries carry out information repackaging strategies by making information repackaging the library’s flagship program and the librarian's main job, understanding the information behavior of the library's native digital users, disseminating digital information packages through social media and collaborative networks, changing the librarian’s role into social librarians and public knowledge and implementing a Marketing and Public Relations (MPR) strategy to disseminate information repackaged products to users. The head of the library plays an important role in supporting librarians in carrying out information repackaging activities. This research concludes that the librarian strategy of repacking information in the new normal era is needed to improve library services that are more creative, interactive, and innovative, in accordance with the user's information needs.